The Convergence of Accounting Treatment for Intangible Assets in Albania - Xhaferri, Shqipe (Richtmann Publishing, 2013)
This study aims at analysing the accounting treatment for identifiable intangible assets. Our research is based on the analysisof the Albania regulation under the current General Accounting Plan of 2003 (from now on referred to as PGC-2003) and theinternational regulations stated by two important accounting regulation organisms: the International Accounting StandardsBoard (IASB) and the Financial Accounting Standards Board (FASB). In particular, we will carry out a comparative study of thedefinition, recognition criteria, valuation, amortisation, impairment of value as well as its recovery and information to beprovided in the Notes to the Financial Statements. The review of these accounting regulations shows that there is nohomogeneous treatment, despite the great advance achieved on this subject, to obtain a higher level of convergence.